Chemistry - Overby, Jason, 1970-; Chang, Raymond (New York, NY : McGraw Hill LLC, 2024)
"The fifteenth edition continues a long tradition of providing a firm foundation in the concepts of chemical principles while instilling an appreciation of the important role chemistry plays in our daily lives. We believe that it is our responsibility to assist both instructors and students in their pursuit of this goal by presenting a broad range of chemical topics in a logical format. At all times, we strive to balance theory and application and to illustrate principles with applicable examples whenever possible"--
Includes index.
Ages 18+
Grades 10-12
Keywords: Chemistry -- Textbooks